KONSEP PENDIDIKAN ISLAM DALAM KELUARGA DAN SEKOLAH MENURUT PROF. DR. ZAKIYAH DARADJAT - Bunyamin (Jurnal Pendidikan Islam, 2021)
Education is an important thing in life, so that its continuity can be found in various environments. Indonesia is familiar with the Tri Education Center, which is education that takes place in the family, school, and community environment. The purpose of this research is to describe how the concept of Islamic education in families and schools according to Zakiah Daradjat a female Muslim scholar who gave birth to many thoughts for the advancement of Islamic education. This researched uses a qualitative approach with the research library method. The results of this study contain the concept of Islamic education in families and schools according to Zakiah Daradjat which includes 4 aspects: the idea of ​​Islamic religious education according to Zakiah Daradjat, the concept of Islamic education in the family, the concept of Islamic education in families and schools, and components of the moral formation when educating children in the family.